Composite photocatalyst as well as preparation method and application thereof
By using a composite photocatalyst that wraps silver phosphate nanoparticles with graphene oxide, the problem of difficulty in decolorizing isononanoic acid in the prior art is solved, and efficient degradation of organic recombinants in isononanoic acid and improvement of product quality is achieved.
Patent Information
- Application Number
- CN202411786341.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing photocatalysts are difficult to effectively remove organic recombinant components from isononanoic acid, and they cannot achieve decolorization of isononanoic acid, which affects product quality.
A composite photocatalyst with graphene oxide wrapped in silver phosphate nanoparticles is used to regulate the ratio of graphene oxide and silver phosphate, and the activity and stability of the catalyst are improved, thereby enhancing the degradation ability of the organic recombinant components in isononanoic acid.
The efficient degradation of organic recombinants in isononanoic acid was achieved, and the successful decolorization of isononanoic acid was improved, and the transparency and quality of the product were reduced while reducing the cost of the catalyst.
Smart Images

Figure CN119425746A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalysts for degrading organic matter, and in particular to a composite photocatalyst and a preparation method and application thereof. Background Art
[0002] In recent years, the degradation of organic matter in wastewater has attracted widespread attention. To this end, many methods have been developed and applied to the degradation of organic pollutants, such as biological treatment, physical treatment and photocatalytic treatment. Due to the complex composition of organic pollutants, the difficulty in degradation, and the characteristics of biological toxicity, the biodegradation technology has limitations and is not economically feasible. Traditional physical treatment technology is non-destructive and only transfers pollutants to another location or another phase, which has potential dangers and the risk of secondary effluent of toxic substances. Semiconductor photocatalytic degradation is considered to be a clean, economical, environmentally friendly and potential technology for the complete degradation of organic pollutants because of its advantages such as non-toxicity, mild reaction conditions and wide catalytic range. Therefore, the technology of semiconductor photocatalytic degradation of organic pollutants has gradually become a research hotspot in today's environmental science.
[0003] Semiconductor photocatalytic degradation reactions are based on semiconductor energy band theory. The general process is as follows: First, the catalyst absorbs incident photons with energy greater than or equal to the band gap of the semiconductor photocatalyst, generating photoexcited electrons at the semiconductor conduction band and the same number of holes at the valence band; these electrons and holes participate in reduction and oxidation reactions, respectively. The generated holes extract electrons from the adsorbed pollutants or react with H2O to form ·OH; on the other hand, the electrons in the conduction band reduce the adsorbed oxygen to form ·O2-, an intermediate with high oxidation performance that further oxidizes organic pollutants.
[0004] Isononanoic acid (3,5,5-trimethyl-1-hexanoic acid) can be obtained by oxidation from isononanal, which is a kind of organic matter. Due to the unique properties of high-branched isononanoic acid such as excellent wettability, permeability and emulsification, isononanoic acid has important uses in lubricants, industrial detergents and other industries. Currently, industrial isononanoic acid is yellow due to the presence of a small amount of organic heavy components, which greatly affects the quality of the product. However, the current photocatalytic degradation reaction cannot effectively remove the heavy components in isononanoic acid, and it is impossible to achieve the decolorization of isononanoic acid.
[0005] Semiconductor silver phosphate has the advantages of strong oxidation ability, high quantum yield, and efficient degradation of organic pollutants. It has attracted widespread attention from scientific researchers and has been applied to the degradation of organic pollutants. However, due to the low solubility of semiconductor silver phosphate in water and the susceptibility to photocorrosion, its environmental application has been greatly reduced. To this end, researchers have been working tirelessly to improve its stability, such as preparing silver phosphate with different morphologies, ion doping, and metal deposition modification; however, the stability of semiconductor silver phosphate still has not achieved the expected effect.
[0006] Graphene oxide has become a carrier for many semiconductors due to its excellent physical and chemical properties, such as good electrical conductivity and optical properties, corrosion resistance, etc. Studies have shown that graphene oxide can not only improve the photocatalytic performance of semiconductor catalysts, but also enhance the stability of semiconductors, which is of great significance to the development of photocatalytic decomposition of organic matter. Summary of the invention
[0007] The purpose of the present application is to overcome the shortcomings of the above-mentioned prior art and provide a composite photocatalyst and its preparation method and application. The composite photocatalyst prepared in the present application can effectively remove the heavy components in isononanoic acid, increase the transparency of isononanoic acid, and further improve the quality of lubricants, industrial detergents and other products to a certain extent, thereby obtaining higher economic benefits.
[0008] To achieve the above purpose, the technical solution adopted by this application is:
[0009] In a first aspect, the present application provides a composite photocatalyst, the composite photocatalyst comprising graphene oxide and silver phosphate particles, wherein the graphene oxide is wrapped on the surface of the silver phosphate nanoparticles;
[0010] The mass ratio of the graphene oxide to the silver phosphate nanoparticles is (1% to 10%):1.
[0011] After extensive research and experiments, the inventors of this application found that a composite photocatalyst can be obtained by adjusting the ratio of graphene oxide and silver phosphate nanoparticles. When silver phosphate is irradiated with light, it is excited to generate photogenerated electron-hole pairs. Graphene oxide has excellent conductivity and can effectively promote the separation efficiency of photogenerated electron-hole pairs in silver phosphate, so that more electrons participate in the degradation reaction of isononanoic acid, thereby enhancing the activity and stability of the composite photocatalyst. In addition, graphene oxide has a large specific surface area, and the electrons stored on its surface can undergo a reduction reaction with the O2 adsorbed on its surface to generate ·O2 - , O2 - The species also has strong oxidizing properties, and further undergoes oxidation reactions with the heavy components in isononanoic acid. The composite catalyst of the present application exhibits efficient and stable photocatalytic degradation of organic heavy components in isononanoic acid, and the content of graphene oxide used in the composite photocatalyst of the present application is very low (1% to 10%), which reduces the cost of the catalyst and can simultaneously achieve decolorization of isononanoic acid, thereby improving the transparency of the product prepared from isononanoic acid.
[0012] When the mass ratio of graphene oxide and silver phosphate nanoparticles exceeds (1% to 10%): 1, the low content of silver phosphate will reduce the absorption effect of light, resulting in a decrease in the generation of electron-hole pairs, thereby reducing the oxidation ability of the catalyst, indicating that the higher the content of graphene oxide, the better.
[0013] As a preferred embodiment of the composite photocatalyst described in the present application, the mass ratio of the graphene oxide to the silver phosphate nanoparticles is (5% to 10%):1.
[0014] More preferably, the mass ratio of the graphene oxide to the silver phosphate nanoparticles is 7%:1.
[0015] When graphene oxide and silver phosphate nanoparticles are used in the above mass ratio, the prepared composite catalyst exhibits efficient and stable photocatalytic degradation of organic heavy components in isononanoic acid, with a chromaticity of 0, successfully achieving the decolorization of isononanoic acid and greatly improving the transparency of the product.
[0016] In a second aspect, the present application provides a method for preparing the composite photocatalyst, comprising the following steps:
[0017] 1) Add flake graphite and KMnO4 to a concentrated sulfuric acid solution containing NaNO3, stir and mix to obtain a gray-brown substance, then add water to raise the temperature for a medium-temperature reaction to obtain a brown substance;
[0018] 2) mixing the brown substance obtained in step 1) with an aqueous solution of hydrogen peroxide, reacting at high temperature under stirring to obtain a yellow suspension, then centrifuging and filtering, taking the precipitate and diluting it to obtain a graphene oxide solution;
[0019] 3) adding the silver nitrate solution to the graphene oxide solution in step 2) and mixing to obtain a mixed solution;
[0020] 4) Adding an aqueous solution of Na2HPO4·12H2O to the mixed solution in step 3) to obtain a yellow precipitate, that is, a composite photocatalyst.
[0021] Commercial graphene layers are thick and have a small specific surface area, which is not conducive to the photocatalytic reaction. In the synthesis process of graphene oxide, NaNO3 and KMnO4 are first reacted at a medium temperature, making the reaction easy to control and the reaction time long, and then a high-temperature reaction is carried out.
[0022] As a preferred embodiment of the method for preparing the composite photocatalyst described in the present application, the temperature in step 1) is maintained at 30-40°C; and the high temperature in step 2) is maintained at 80-105°C.
[0023] As a preferred embodiment of the method for preparing the composite photocatalyst described in the present application, the solvent in the silver nitrate solution is ethanol and deionized water, and the ratio of the two is 1:1; the volume ratio of hydrogen peroxide to water in the aqueous solution of hydrogen peroxide is 1:2.
[0024] As a preferred embodiment of the method for preparing the composite photocatalyst described in the present application, the mass ratio of the flake graphite to KMnO4 is 1:3.
[0025] As a preferred embodiment of the method for preparing the composite photocatalyst described in the present application, in the step 4), the brown substance and the aqueous solution of hydrogen peroxide are reacted in the dark.
[0026] As a preferred embodiment of the method for preparing the composite photocatalyst described in the present application, the content of graphene oxide in the composite photocatalyst is 1% to 10%, preferably 7%.
[0027] In some embodiments, in some embodiments, the concentration of concentrated sulfuric acid is 98%.
[0028] In some embodiments, in the step 1), flake graphite and KMnO4 are added to a concentrated sulfuric acid solution containing NaNO3 and mixed, and the temperature is maintained at about 10°C; the temperature is then raised to 40°C, and stirring is continued to obtain a gray-brown substance; water is added to the gray-brown substance to continue the reaction, and then the temperature is raised and controlled to 90°C to obtain a brown substance.
[0029] The one-step method (one-step mixing of the prepared solution) is an important step in the preparation process of the composite photocatalyst applied by the present invention. The prepared composite catalyst has a complete crystal form and good optical properties. The introduction of graphene oxide not only improves the degradation efficiency of silver phosphate on the organic heavy components in isononanoic acid, but also improves the stability of silver phosphate. When the mass ratio of graphene oxide to silver phosphate nanoparticles is 7%:1, the organic heavy components can be completely degraded, the chromaticity of the isononanoic acid product is 0, and the isononanoic acid is transparent, which greatly improves the quality of the product.
[0030] In a third aspect, the present application provides the use of the above-mentioned composite photocatalyst in photocatalysis of isononanoic acid.
[0031] As a preferred embodiment of the application described in the present application, the composite photocatalyst photocatalytically degrades organic heavy components in isononanoic acid.
[0032] Compared with the prior art, this application has the following beneficial effects:
[0033] The present application provides a composite photocatalyst and its preparation method and application. The composite photocatalyst of the present application introduces a very low amount of graphene oxide, which has certain advantages in production cost compared with the deposition of other precious metals. The composite photocatalyst uses a one-step method to construct a package structure of silver phosphate and graphene oxide, and the process flow is simple and easy to operate. At the same time, because graphene oxide has a high specific surface area, the electrons stored on its surface can react with the oxygen adsorbed on its surface to generate highly oxidizing ·O2 - Species, further help to improve the degradation of organic matter. The composite catalyst prepared by adjusting the ratio of graphene oxide and silver phosphate in this application shows stable and efficient photocatalytic degradation of heavy components in isononanoic acid, and successfully achieves the decolorization of isononanoic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the scanning electron microscope image of the composite photocatalyst GO / Ag3PO4;
[0035] Figure 2 The product chromatogram of the effect of composite photocatalysts formed by different graphene oxides on isononanoic acid (some fonts are unclear and do not affect the substantive content);
[0036] Figure 3 This is the result diagram of the photocatalytic degradation of the heavy components in the isononanoic acid product by the composite photocatalyst GO / Ag3PO4 (from right to left are the isononanoic acid product and the effect diagram of the product photocatalysis for 30 minutes and 1 hour). DETAILED DESCRIPTION
[0037] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0038] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0039] Example 1. Preparation of composite photocatalyst
[0040] The embodiment of the present application provides a composite photocatalyst, and the preparation method thereof comprises the following steps:
[0041] 1) Place a 250mL beaker in an ice bath, add 120mL of 98% concentrated sulfuric acid, and then add 2.5g of NaNO3 powder while stirring continuously.
[0042] 2) While the solution is constantly stirring, slowly add 5 g of flake graphite and 15 g of KMnO4, respectively, and continue stirring for 1 hour, keeping the temperature at around 30°C.
[0043] 3) Remove the ice bath, raise the temperature to 55°C, and continue stirring to obtain a gray-brown substance.
[0044] 4) On the basis of step 3), 25 mL of pure water was added to continue the reaction for a period of time, the reaction conditions were controlled at 95° C., the reaction time was 15 min, and a brown substance was obtained.
[0045] 5) Continue to add 17 mL of hydrogen peroxide and 34 mL of pure water mixture. At this time, bubbles emerge and the suspension gradually turns yellow. Stop the reaction when there are no bubbles to obtain a yellow suspension solution.
[0046] 6) The obtained yellow suspension was washed with 1 mol / L hydrochloric acid, centrifuged and filtered to remove sulfate ions.
[0047] 7) The filtered precipitate is washed with pure water for multiple times, precipitated, centrifuged, and finally the precipitate is diluted to the required concentration of 1 mg / mL to obtain a graphene oxide (GO) solution.
[0048] 8) 350 μL of the prepared graphene oxide solution was measured, 10 mL of pure water was added, and ultrasonication was performed for 0.5 h to ensure that the graphene oxide was fully and evenly dispersed.
[0049] 9) Dissolve 2.04 g of silver nitrate in a mixture of 20 mL of pure water and ethanol, stir thoroughly to dissolve, and add dropwise to the GO dispersion in 8) to prepare solution A.
[0050] 10) Dissolve 1.432 g of Na2HPO4·12H2O in pure water and stir thoroughly to dissolve to prepare solution B.
[0051] 11) Add solution B dropwise into solution A and continue stirring in a dark place for 1 hour.
[0052] 12) The yellow precipitate obtained above was washed with water for several times, and after centrifugation, the precipitate was dried at 60°C for 12 hours under vacuum to obtain a composite photocatalyst, wherein the mass ratio of graphene oxide to silver phosphate was 7%:1. The sample was recorded as composite photocatalyst 7% GO / Ag3PO4, and its scanning electron microscope image was as follows: Figure 1 shown.
[0053] Example 2
[0054] This embodiment 2 provides a composite photocatalyst. Compared with embodiment 1, the difference is that the ratio of graphene oxide and silver phosphate is different, specifically:
[0055] Example 1 In step 8), 250 μL of the prepared GO solution was measured, 10 mL of pure water was added, and the mixture was ultrasonicated for 0.5 h to fully and evenly disperse the graphene oxide. The remaining steps and parameters were the same as those in Example 1. The mass ratio of graphene oxide to silver phosphate in the prepared composite photocatalyst was 5%:1. The sample was recorded as composite photocatalyst 5% GO / Ag3PO4.
[0056] Example 3
[0057] This embodiment 2 provides a composite photocatalyst. Compared with embodiment 1, the difference is that the ratio of graphene oxide and silver phosphate is different, specifically:
[0058] Example 1 In step 8), 500 μL of the prepared GO solution was measured, 10 mL of pure water was added, and the mixture was ultrasonicated for 0.5 h to fully and evenly disperse the graphene oxide. The remaining steps and parameters were the same as those in Example 1. The mass ratio of graphene oxide to silver phosphate in the prepared composite photocatalyst was 10%:1. The sample was recorded as composite photocatalyst 10% GO / Ag3PO4.
[0059] Example 4
[0060] This embodiment 2 provides a composite photocatalyst. Compared with embodiment 1, the difference is that the ratio of graphene oxide and silver phosphate is different, specifically:
[0061] Example 1 In step 8), 50 μL of the prepared GO solution was measured, 10 mL of pure water was added, and the mixture was ultrasonicated for 0.5 h to fully and evenly disperse the graphene oxide. The remaining steps and parameters were the same as those in Example 1. The mass ratio of graphene oxide to silver phosphate in the prepared composite photocatalyst was 1%:1. The sample was recorded as composite photocatalyst 1% GO / Ag3PO4.
[0062] Comparative Example 1
[0063] Compared with Example 1, the difference of Comparative Example 2 is that the preparation method does not adopt steps 1)-7), specifically: 100 mg of commercial graphene oxide nanomaterial (purchased from Aladdin official website) is dissolved in 100 mL of water, ultrasonicated for 1 hour, so that the graphene oxide is fully and evenly dispersed to obtain a graphene oxide (GO) solution, and the remaining steps and parameters are the same as those in Example 1. The mass ratio of graphene oxide to silver phosphate is 7%:1. For the convenience of distinction, the sample is recorded as M-GO / Ag3PO4.
[0064] Comparative Example 2
[0065] Compared with Example 1, the difference of Comparative Example 3 is that silver sulfate is used instead of silver phosphate, and the remaining steps and parameters are the same as those of Example 1. For the convenience of distinction, the sample is recorded as S-GO / Ag3PO4.
[0066] Comparative Example 3
[0067] Compared with Example 1, the difference of Comparative Example 3 is that method steps 9)-10) are different, and the remaining steps and parameters are the same as those of Example 1. Specifically:
[0068] 9) Dissolve 1.432 g of Na2HPO4·12H2O in pure water and stir thoroughly to dissolve, and then add dropwise to the above GO dispersion to prepare solution A.
[0069] 10) 2.04 g of silver nitrate was dissolved in a mixture of 20 mL of pure water and ethanol and stirred thoroughly to prepare solution B. The mass ratio of graphene oxide to silver phosphate was 7%:1. For easy distinction, the sample was recorded as P-GO / Ag3PO4.
[0070] Test Example 1: Performance Evaluation
[0071] In this test, the composite photocatalysts obtained in Examples 1-4 and Comparative Examples 1-3 were used to evaluate the performance of photocatalytic degradation of organic heavy components in isononanoic acid.
[0072] The photocatalytic degradation experiment was carried out at room temperature and pressure, and the light source was a xenon lamp (250W). The specific experimental process is as follows:
[0073] Weigh 50 mg of the prepared composite photocatalyst and 1.5 L of isononanoic acid into a 2 L beaker (the beaker is completely wrapped with tin foil). Place the beaker containing the isononanoic acid liquid on a stirrer and place it in the center of the illumination range, and control the stirring speed to be constant (the speed is 500 rpm). After 30 minutes of dark reaction, use a syringe to take about 3 ml of liquid and filter out the catalyst particles. Turn on the light source and take samples every 30 minutes under xenon light to filter out the catalyst. Perform liquid chromatography analysis on the samples taken.
[0074] The composite photocatalyst prepared in Example 1-4 was used as a degradation catalyst, and continuous illumination was performed for sampling. It was finally found that the color of the product isononanoic acid became lighter after 30min-2h of illumination using catalysts with different contents of graphene oxide, while after 30min and 1h of photocatalytic degradation of GO / Ag3PO4, the yellow color in isononanoic acid gradually turned into light yellow, and finally the color disappeared and became colorless and transparent. The product composition was detected by gas chromatography, and it was found that the chromatographic peaks of some heavy components in isononanoic acid disappeared.
[0075] Table 1 Photocatalytic degradation and decolorization effects of different catalysts
[0076]
[0077] Control experiment
[0078] Without adding any catalyst, add 1.5L of isononanoic acid into a 2L beaker (the beaker is completely wrapped with tin foil). Place the beaker containing the isononanoic acid liquid on a stirrer and place it in the center of the illumination range, and control the stirring speed to be constant (the speed is 600rpm). After 30 minutes of dark reaction, take about 3ml of liquid with a syringe and filter out the catalyst particles. Turn on the light source and take samples every 30 minutes under xenon light illumination. Perform liquid chromatography analysis on the samples taken. The results show that the color of isononanoic acid has not changed at all, and the chromatograms before and after illumination have almost no change.
[0079] Control experiment
[0080] Weigh 50 mg of the composite photocatalyst 7% GO / Ag3PO4 prepared in Example 1 and 1.5 L of isononanoic acid and add them to a 2 L beaker (the beaker is completely wrapped with tin foil). Place the beaker containing the isononanoic acid liquid on a stirrer and place it in the center of the illumination range, and control the stirring speed to be constant (the rotation speed is 600 rpm). After 30 minutes of dark reaction, filter out the catalyst particles. The light source is no longer turned on, and samples are taken every 30 minutes. The samples are subjected to liquid chromatography analysis. The results show that the color of isononanoic acid has not changed at all, and the chromatogram before and after illumination has hardly changed.
[0081] The combined analysis of the sampling results and chromatograms of the control experiment and the control experiment shows that catalyst and light are necessary conditions for the decolorization of isononanoic acid. Catalyst and light, that is, photocatalytic degradation, make the color of isononanoic acid lighter and even transparent, and the heavy components in isononanoic acid are effectively decomposed.
[0082] Figure 1 The product chromatogram of isononanoic acid shows that when 7% GO / Ag3PO4 catalyst is added, the peak at the rhombus almost disappears. When the GO content is increased to 10%, the peak at the rhombus almost does not change. This indicates that the best effect is achieved when the GO content is 7%.
[0083] Figure 2 The results of the composite photocatalyst 7% GO / Ag3PO4 photocatalytic degradation of the heavy components in the isononanoic acid product are shown in Figure 1. From right to left, the isononanoic acid product, the product photocatalytic effect of 30min and 1h. This result shows that the 7% GO / Ag3PO4 composite photocatalyst has good catalytic performance for the degradation of the heavy components in isononanoic acid.
[0084] The present application discloses a preparation method and application of a composite photocatalyst of graphene oxide wrapped on the surface of silver phosphate nanoparticles. In the process of the catalyst method, a wrapping structure is constructed by adjusting the ratio of graphene oxide and silver phosphate. The prepared composite catalyst exhibits stable and efficient photocatalytic degradation of heavy components in isononanoic acid, and successfully achieves decolorization of isononanoic acid.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A composite photocatalyst, characterized in that: The composite photocatalyst comprises graphene oxide and silver phosphate particles, wherein the graphene oxide is wrapped on the surface of the silver phosphate nanoparticles; The mass ratio of the graphene oxide to the silver phosphate nanoparticles is (1% to 10%):
1.
2. The composite photocatalyst according to claim 1, characterized in that The mass ratio of the graphene oxide to the silver phosphate nanoparticles is 7%:
1.
3. A method for preparing a composite photocatalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: 1) Add flake graphite and KMnO4 to a concentrated sulfuric acid solution containing NaNO3, stir and mix to obtain a gray-brown substance, then add water to raise the temperature for a medium-temperature reaction to obtain a brown substance; 2) mixing the brown substance obtained in step 1) with an aqueous solution of hydrogen peroxide, reacting at high temperature under stirring to obtain a yellow suspension, then centrifuging and filtering, taking the precipitate and diluting it to obtain a graphene oxide solution; 3) adding the silver nitrate solution to the graphene oxide solution in step 2) and mixing to obtain a mixed solution; 4) Adding an aqueous solution of Na2HPO4·12H2O to the mixed solution in step 3) to obtain a yellow precipitate, that is, a composite photocatalyst.
4. The preparation method according to claim 3, characterized in that: The temperature in step 1) is maintained at 30-40°C; the temperature of the high temperature in step 2) is maintained at 80-105°C.
5. The preparation method according to claim 3, characterized in that: The solvents in the silver nitrate solution are ethanol and deionized water, and the ratio of the two is 1:1; the volume ratio of hydrogen peroxide to water in the aqueous solution of hydrogen peroxide is 1:
2.
6. The preparation method according to claim 3, characterized in that: The mass ratio of the flake graphite to KMnO4 is 1:
3.
7. The preparation method according to claim 3, characterized in that: In the step 4), the brown substance and the aqueous solution of hydrogen peroxide are reacted in the dark.
8. The preparation method according to claim 3, characterized in that: The mass concentration of graphene oxide in the composite photocatalyst is 1% to 10%.
9. Use of the composite photocatalyst as claimed in claim 1 or 2 in photocatalysis of isononanoic acid.
10. The use according to claim 11, characterized in that The composite photocatalyst photocatalytically degrades organic heavy components in isononanoic acid.
Citation Information
Patent Citations
Graphene oxide / silver phosphate composite photocatalyst as well as preparation method and application thereof
CN106890657A
Method for preparing silver phosphate / graphene oxide visible light photocatalyst by low temperature liquid phase precipitation method
CN110227511A
Preparation method of alkyne type graphene oxide-lithium antimonate-silver antimonate composite material
CN116328767A
Reduced graphene oxide-silver phosphate (RGO-agp) and a process for the preparation thereof for the photodegradation of organic dyes
US20160144349A1